Higher insulin sensitivity in EDL muscle of rats fed a low-protein, high-carbohydrate diet inhibits the caspase-3 and ubiquitin-proteasome proteolytic systems but does not increase protein synthesis - Santos, Maisa Pavani dos; Batistela, Emanuele; Pereira, Mayara Peron; Paula-Gomes, Silvia; Zanon, Neusa Maria; Kettelhut, Isis do Carmo; Karatzaferi, Christina; Balbinotti Andrade, Claudia Marlise; Franca, Suelem Aparecida de; Baviera, Amanda Martins [UNESP]; Kawashita, Nair Honda (Elsevier B.V., 2016)
Compared with the extensor digitorum longus (EDL) muscle of control rats (C), the EDL muscle of rats fed a low-protein, high-carbohydrate diet (LPHC) showed a 36% reduction in mass. Muscle mass is determined by the balance between protein synthesis and proteolysis; thus, the aim of this work was to evaluate the components involved in these processes. Compared with the muscle from C rats, the EDL muscle from LPHC diet-fed rats showed a reduction (34%) in the in vitro basal protein synthesis and a 22% reduction in the in vitro basal proteolysis suggesting that the reduction in the mass can be associated with a change in the rate of the two processes. Soon after euthanasia, in the EDL muscles of the rats fed the LPHC diet for 15 days, the activity of caspase-3 and that of components of the ubiquitin-proteasome system (atrogin-1 content and chymotrypsin-like activity) were decreased. The phosphorylation of p70(S6K) and 4E-BP1, proteins involved in protein synthesis, was also decreased. We observed an increase in the insulin-stimulated protein content of p-Akt. Thus, the higher insulin sensitivity in the EDL muscle of LPHC rats seemed to contribute to the lower proteolysis in LPHC rats. However, even with the higher insulin sensitivity, the reduction in p-E4-BP1 and p70(S6K) indicates a reduction in protein synthesis, showing that factors other than insulin can have a greater effect on the control of protein synthesis. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Low-protein; high-carbohydrate diet; Protein synthesis; Proteolytic pathways; Extensor digitorum longus; Insulin sensitivity; Growing rats